Characteristics of hospitalised patients with influenza in 2015–2016 in northern Israel: three circulating strains and continued fear of 2009 A/H1N1. (2019) - Kalish, Tomer; Miron, Dan; Azrad, Maya; Rechnitzer, Hagai; Ben-Amram, Hila; Glikman, Daniel; Peretz, Avi
Abstract: This study aimed to characterise children and adults diagnosed with influenza who were admitted to three medical centres in northern Israel in the winter of 2015–2016, a unique season due to infection with three types of influenza strains: A/H1N1, A/non-H1N1 and B. Data were collected retrospectively from medical records. Influenza A/H1N1 infected mainly adults (61% vs. 16% in children, P < 0.001) while influenza B was the common type in children (54% vs. 28% in adults, P < 0.001). Adults (36% vs. 5% in children, P < 0.001) and patients infected with A/H1N1 had higher rates of pneumonia (34% vs. 16% and 14% in influenza B and A/non-H1N1, respectively, P = 0.002). Treatment with oseltamivir was prescribed to 90% of patients; adults had higher rates of treatment (96% vs. 84% in children, P = 0.002) as well as patients infected with A/H1N1 (96% vs. 86% in influenza B and A/non-H1N1, respectively, P = 0.04). Oseltamivir was given after a mean of 3.6 days of symptoms. Preferential infection of adults by A/H1N1 was evident in Israel in 2015–2016; pneumonia rates were higher in adults and in A/H1N1-infected patients. Oseltamivir was prescribed to most patients but especially to those infected with A/H1N1, and was given relatively late in the course of the disease.